2014
DOI: 10.5812/jjm.13120
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory to Clinical Investigation of Carbapenem Resistant Acinetobacter baumannii Outbreak in a General Hospital

Abstract: Background:The number of reported cases, infected with carbepenem resistant Acinetobacter baumannii (CRAb) and multi-drug resistant (MDR) Acinetobacter species had gradually increased in most PLA general hospital wards from April to June in 2007.Objectives:We have described the investigation of an outbreak of CRAb and MDR Acinetobacter in PLA general hospital, Beijing. The prospective and retrospective findings were identified and analyzed to study the infection causes.Materials and Methods:A. baumannii sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Details are shown in Ref 6. Pseudomonas aeruginosa ATCC27853 and Escherichia coli ATCC25922 were used as the quality-control isolates ( 5 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details are shown in Ref 6. Pseudomonas aeruginosa ATCC27853 and Escherichia coli ATCC25922 were used as the quality-control isolates ( 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is also located on the skin of healthy human. Acinetobacter baumannii strains are able to survive for a long time even on a dry surface and some of them could toughly attach to human epithelial cells through fimbriae or side chains ( 5 ). These characteristics indicate that A. baumannii could easily spread via surface, air or any other possible pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Ambrosi et al, 33 found 31 A. baumannii isolates grouped into 3 subtypes (A, B, and C). Guo-Xin et al, 29 found 62 A. baumannii isolates representing 9 different clones. Hammerun et al, 28 detected 4 different PFGE profiles in 8 investigated isolates and found 4 of the isolates were related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial susceptibility patterns of the isolates were assessed using the Kirby-Bauer disk diffusion method on Mueller-Hinton Agar as described by the Clinical and Laboratory Standards Institute (CLSI) (12,13) guideline. All the isolates were sub-cultured from freezer stocks on sheep blood agar to prepare inoculum suspension.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%